An Analysis of Authentic Assessment Integrated in Moral and Social Aspects of English Classes at A State Junior High School in Indramayu - Risma Mutiasari; Rini Susanti Wulandari (Dinasti Publisher, 2025)
This study examines the integration of authentic assessment into the moral and social dimensions of English language learning at SMPN Unggulan Sindang, Indramayu. The research objectives are threefold: (1) to describe the implementation of authentic assessment in English classes with a focus on moral and social aspects, (2) to identify challenges encountered by teachers and students in its application, and (3) to analyze its relevance and contribution to students' character education. Adopting a qualitative descriptive approach, data were gathered through classroom observations, semi-structured interviews, document analysis, and triangulation to enhance validity. The findings indicate that authentic assessment is enacted via project-based learning, reflective reading, group discussions, peer and self-assessments, and summative reports that evaluate both cognitive skills and character traits. Teachers design activities that promote honesty, discipline, cooperation, empathy, and responsibility while advancing language proficiency. This integration aligns with Lickona's (1991) framework of moral knowing, moral feeling, and moral action, positioning English as a vehicle for character development. Nonetheless, obstacles include time constraints, inconsistent student engagement, and teachers' insufficient training in creating character-oriented rubrics and evaluations. In summary, incorporating authentic assessment into moral and social aspects of English learning substantially supports holistic student development by cultivating reflective thinking, moral awareness, and social competencies alongside linguistic abilities. The study recommends institutionalizing authentic assessment as a sustainable practice to reinforce character education within English language teaching and learning.